Financial Performance's Impact on Firm Value: How Managerial Ownership Mediates the Relationship - Kristanti, Farida Titik; Nurhayati, Imas; Fariska, Putri (Journal of Ecohumanism, 2024)
Banks play a significant role in facilitating the generation of economic growth opportunities, which can impact the achievement of government-set economic growth objectives. Hence, it is imperative to foster a climate that promotes banks' competitive growth and resilience, enabling them to effectively confront many problems in the face of escalating global complexities. To maintain a competitive edge, the bank must exhibit strong performance that positively influences corporate value. For that, the objective of this study is to ascertain the key determinants that exert a substantial impact on the valuation of firms, specifically examining the potential influence of capital structure, profitability, profits per share, and dividend payout ratio on the value of financial institutions. Another aim of the study is to ascertain the potential moderating effect of managerial ownership on the independent variable of company value. The sample selection included purposive random sampling, with the criterion of including only those with complete data from the research period spanning 2011 to 2022, using Moderation Regression and data panel Analysis. This study shows that earnings per share and dividend payout ratio significantly impact banks' valuation. In the interim, the Moderation Regression Analysis has yielded findings indicating that management ownership is a moderating factor in the relationship between earnings per share and banking value.